Tantangan Dan Peluang Moderasi Beragama Di Era Digital - Resti Paujiah; Hasna Latipah Afifah; Parhan Muhamad; Fiqra Muhamad Nazib (Yayasan Al-Afif, 2024)
This study aims to analyze the literature on the challenges and opportunities for religious moderation in the digital era. The study uses a Systematic Literature Review with the stages of selecting titles, collecting, selecting articles, analyzing, synthesizing, and organizing writing. The study used 26 articles from a selection of 37 articles. The focus of the study is 3 things, namely challenges, opportunities, and religious moderation in the digital era. The results of the study show: 1) The main challenge of religious moderation is the influence of social media, which can increase radicalization, intolerance and negative perceptions of moderation. 2) Opportunities for religious moderation have great potential to create social harmony, especially in the current technological era, by spreading positive content that encourages tolerance, diversity, and peace. 3) Religious moderation in the digital era emphasizes the importance of national values, awareness of diversity to maintain social balance.